Change Passport and Passport Application Electronics for Security and Convenience Service Immigration - Nila Muhedina Simarmata; Janpatar Simamora (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Immigration is related to the traffic of people entering or leaving Indonesian territory and its supervision to maintain state sovereignty. Immigration functions include providing immigration services, law enforcement, and maintaining the security and comfort of the country, while contributing to the development of community welfare. With the increase in crimes involving fake identities or misuse of other people's identities, immigration must be stricter in checking travel documents used by Indonesian citizens and foreign nationals when entering and leaving Indonesian territory. Therefore, immigration introduced a new passport design and implemented the use of electronic passports. The research method used in this research is a descriptive qualitative method. The research results show that changes in passport design can increase state sovereignty and security, because the new design is difficult to imitate. This can be seen from the materials used in making the new passports as well as the designs that highlight elements of Indonesian culture. Applying for an electronic passport does require higher costs than a regular passport, but offers advantages that conventional passports do not have, including a better level of security. Using an electronic passport also makes it easier for the holder to undergo immigration service administration because this passport uses a biometric system that only needs to be scanned.